Study of The Effect of Concentration on The Level of Wetness in Chicory Leaves Using The ADSA-Overlay Method - Mulyono, Tri; Ahmad Turidi; Bambang Piluharto; Dwi Indarti; Sudarko; D. Iwan Setiawan (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
It is challenging to distinguish between farmers and insecticides. Chemicals called pesticides are applied to eliminate pests in order to boost agricultural production for farmers. Using the Axisymmetric Drop Shape Analysis (ADSA)-Overlay approach, this study attempts to investigate the impact of the pesticide fipronil concentration on the degree of wetness in mustard leaves. The size of the contact angle between the mustard leaf surface and the pesticide solution determines the pesticide's wetting action. The cosine of the contact angle (θ) between the liquid insecticide and the solid surface determines the surface tension (γ). Sessile drop is the method used to assess surface tension. Chicory is the surface area that comes into touch with pesticide drops. At 25oC samples containing 50 ppm were poured onto mustard leaves using a syringe. A digital microscope that was linked to a personal computer was used to capture sessile drop pictures. Three iterations of sessile drop imaging were conducted using samples at temperatures of 27, 29, 31, 33, and 35oC. Samples of pesticide solution at concentrations of 75, 100, 125, and 150 ppm were photographed again. The reagent 50Sc pesticide's wetting level rises with an increase in fipronil content. As concentration increases, the reagent 50Sc insecticide solution's contact angle tends to get smaller.